Evolution of normal electrical resistance in oxygen underdoped Ho₁Ba₂Cu₃O₇₋δ single crystals in the process of application-removal of high hydrostatic pressure - Vovk, R.V.; Khadzhai, G.Ya.; Nazyrov, Z.F. (Functional Materials, 2012)
The influence of high hydrostatic pressure on electrical resistance in afr-plane of oxygen underdoped Ho₁Ba₂Cu₃O₇₋δ has been studied. It was found that high-pressure-in-duced redistribution of labile oxygen leaded to increasing phase separation, which was accompanied by a process of structural relaxation and uphill diffusion in the bulk of the pilot sample. It has been suggested that the generation of low-temperature (oxygen-depleted) phase can occur at twin boundaries. The temperature dependence of the resistivity above Tc can be accurately approximated by the model s-d-electron scattering by phonons. Application of high pressure leads to a decrease of the resistance, which at high temperatures is much larger than at low temperatures. This may be due to the weakening the electron-phonon interaction with increasing pressure.